2015
DOI: 10.1021/jp5118008
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Low-Sensitivity Cast-Melt High-Energy-Density Materials: Synthesis, Characterization, and Decomposition Kinetics of 3,4-Bis(4-nitro-1,2,5-oxadiazol-3-yl)-1,2,5-oxadiazole-2-oxide

Abstract: The most comprehensive approach to analyze and characterize energetic materials is suggested and applied to enable rational, rigorous design of novel materials and targeted improvements of existing materials to achieve desired properties. We report synthesis, characterization of the structure and sensitivity, and modeling of thermal and electronic stability of the energetic, heterocyclic compound, 3,4-bis(4-nitro-1,2,5-oxadiazol-3-yl)-1,2,5-oxadiazole-2-oxide (BNFF). The proposed novel, relatively simple synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 86 publications
4
75
3
Order By: Relevance
“…Also desired are low cost of inputs and of synthesis as well as low environmental impact of both inputs and the products of decomposition. New HEDMs are actively researched experimentally as well as computationally [2][3][4][5][6][7][8][9]. Most effective molecular HEDM contain nitrogen-and oxygen-containing heterocycles and/or NOx moieties [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also desired are low cost of inputs and of synthesis as well as low environmental impact of both inputs and the products of decomposition. New HEDMs are actively researched experimentally as well as computationally [2][3][4][5][6][7][8][9]. Most effective molecular HEDM contain nitrogen-and oxygen-containing heterocycles and/or NOx moieties [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most effective molecular HEDM contain nitrogen-and oxygen-containing heterocycles and/or NOx moieties [10]. The decomposition of such molecules usually leads to the release of COx, NOx and cyanogen molecules which are toxic or environmentally damaging [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The impact, friction, and ESD sensitivity of this material was found to be comparable to pentaerythritol tetranitrate (PETN). BNFF (aka DNTF) can be synthesized depicted in Scheme 17 [50]. Formation of furazan (63) from malononitrile, followed by diazotization and substitution furnished chloroxime (64).…”
Section: Scheme 16 Synthesis Of Dinitro Tetranitrate Ester (62)mentioning
confidence: 99%
“…Exposure of the chloroxime to silver carbonate afforded difurazano furoxan (65), which was nitrated to yield BNFF (66). BNFF (aka DNTF) can be synthesized depicted in Scheme 17 [50]. Formation of furazan (63) from malononitrile, followed by diazotization and substitution furnished chloroxime (64).…”
Section: Scheme 16 Synthesis Of Dinitro Tetranitrate Ester (62)mentioning
confidence: 99%
“…Our recent study 17,25 revealed the four most plausible unimolecular decomposition channels of BNFF and its derivatives, illustrated in Fig. 2: (1) the dissociation of C-NO 2 bond, (2) nitro-nitrite (CONO) isomerization, (3) elimination of CN 2 O 2 through the concerted break of the outer oxadiazol rings, and (4) cleavage of the central ring.…”
Section: Thermal Stability Of Bnff Bnff-1 and Anff-1mentioning
confidence: 99%